2017
DOI: 10.1016/j.jtusci.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Norfloxacin mixed solvency based solid dispersions: An in-vitro and in-vivo investigation

Abstract: Norfloxacin (NF) is a synthetic fluoro-quinolone molecule that is used for the treatment of urinary tract infections. However, due to its poor aqueous solubility, it has low oral bioavailability. The aim of the present study was to improve the aqueous solubility and dissolution profile of NF by formulating its mixed-solvency based solid dispersions (SDs). The NF-loaded SDs were prepared by a solvent evaporation technique using urea, sodium benzoate and a niacinamide hydrotropic mixture. The prepared SDs were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Fluorine (F) and the piperazine group give an extra stabilization to the ternary complex norfloxacin-enzyme-DNA because it interacts with the enzyme; this stabilization is responsible for the effectiveness potential antibacterial action. However, this compound presents poor aqueous solubility that causes a low oral bioavailability, generating a poor metabolization of norfloxacin [5,6]. Garnayak and Patel [4] have reported that less than 10% of the drug containing norfloxacin as active principle is metabolized, part of the drug excreted by renal excretion and a fraction of the drug remained unaltered by the metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorine (F) and the piperazine group give an extra stabilization to the ternary complex norfloxacin-enzyme-DNA because it interacts with the enzyme; this stabilization is responsible for the effectiveness potential antibacterial action. However, this compound presents poor aqueous solubility that causes a low oral bioavailability, generating a poor metabolization of norfloxacin [5,6]. Garnayak and Patel [4] have reported that less than 10% of the drug containing norfloxacin as active principle is metabolized, part of the drug excreted by renal excretion and a fraction of the drug remained unaltered by the metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…The blood samples were centrifuged at 7000 rpm at 4 °C for 20 min to separate plasma. Separated plasma samples were analyzed via the high performance liquid chromatography method as previously reported [28].…”
Section: Pharmacokinetic Evaluationmentioning
confidence: 99%
“…The samples were stored in USP type-1 flint vials and hermetically sealed with bromo butyl rubber plugs with aluminum caps. 25…”
Section: Stability Studymentioning
confidence: 99%